Corruption and COVID-19 - Rose-Ackerman, Susan (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
The coronavirus pandemic has created incentives for corruption, fraud, and self-dealing that can be explained by the underlying political-economic incentives at work. Three characteristics of the COVID-19 crisis are especially important. First, the rapidly unfolding pandemic and the accompanying economic recession have led to fierce competition for essential resources. Second, governments have rapidly mobilized public funds (for both healthcare and economic stabilization) at an unprecedented scale, creating opportunities for rent-seeking of many kinds, including outright corruption. Third, politicians, bureaucrats and medical professionals exercise substantial discretion in the allocation of resources. A lack of transparency and weak oversight and enforcement have exacerbated the problems of corruption and fraud, and public measures against these offenses have not kept pace with the developing crisis. The paper discusses how these features interact in procurement processes, in government assistance to individuals and businesses, and in the development and licensing of pharmaceuticals. Those who benefit from corruption, be they contractors or individuals, will emerge from the pandemic better off than before it started if governments do not act. Tolerance of malfeasance will be at the expense of long-term government legitimacy and spread the virus to the most vulnerable. The need for a speedy response to the pandemic should not be an excuse for undermining institutions that strengthen governmental integrity.